A Mathematical Model in Automatic Control Aerospace Engineering Education. Issue 2 (2020) - Castaldi, P.; Mimmo, N.
Abstract: The aerospace engineering educational system aims to create future professionals able to solve problems of high complexity, with time constraints and which solutions matches prescribed level of performance. In our past work, we introduced the innovative concept of the Professional Readiness Level (PRL) as a unique parameter to quantify how close the students are to the aerospace industry. In this paper we propose a dynamic model, of the PRL, capable to capture, in simple but effective way, the student behaviour we, as professors, observed in our educative experience.